Accelerated ageing and controlled deterioration in beetroot seeds - Silva, J. B. [UNESP]; Vieira, R. D.; Panobianco, M. [UNESP] (International Seed Testing Association, 2006)
It is fundamentally important that adequate tests are used to evaluate the physiological quality of produced and commercialized seeds. The objective of this work was to study accelerated ageing and controlled deterioration to evaluate seed vigour in beetroot, seeking to associate these results with seedling emergence in the field. Consequently, five seed lots of Top Tall Early Wonder cultivar were submitted to the tests of germination, seedling emergence in the field, accelerated ageing (using periods of 24, 48 and 72 hours at 42°C) and controlled deterioration (seeds with moisture contents of 22, 24 and 26% at 41°C and 45°C for 12, 24 and 36 hours). Combinations of 72h at 42°C for the accelerated ageing test and 45°C with 24% moisture content for 24h for the controlled deterioration test were sensitive enough to evaluate the physiological potential of beetroot seeds, providing information that was compatible with results of the seedling emergence in the field.